(untitled) (Research, Society and Development, 2021)
Within the scope of the National School Feeding Program, the provision of meals and snacks to students in public schools occurs through mediation in queues. These represent modes of social organization and access to the right to food. It is proposed to analyze the expressions, symbolic meanings, and behavior of students in the institutional context of the daily routine of the line of school lunches offered in high school in a public school. To get closer to this reality, participant observation is carried out and the analysis is complemented with narratives from students, education professionals and school employees, produced through essays and interviews. The queue is problematized as a place of humiliation, bullying, sexual violence and hunger. It describes the experiences of these students in situations of hunger and food insecurity in the face of acts of implicit, veiled, symbolic gender violence. The lunch line is concluded as a contradictory place to humanist pedagogical practice and the right to school meals.